The power of mandatory quality disclosure: Evidence from the German housing market - Manuel Frondel; Andreas Gerster; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Many countries have introduced Energy Performance Certificates to mitigate the information asymmetry with respect to the thermal quality of houses. Drawing on a stylized theoretical model that is coupled with comprehensive data on real estate advertisements in the German housing market, this paper investigates the causal effect of disclosing energy information on the offer prices of houses. We are particularly interested in testing whether house sellers who would not voluntarily disclose the house's energy consumption decrease the offer price upon a shift to a mandatory disclosure scheme. Employing both within-variation from panel data and an instrumental-variable approach to cope with the endogeneity of disclosure decisions, our analysis demonstrates the power of mandatory disclosure rules to increase market transparency and to reduce prices. – – In vielen Ländern wurden Gebäudeausweise eingeführt, um Informationsasymmetrien zwischen Käufern und Verkäufern in Bezug auf die Energieeffizienz von Häusern zu verringern. Gestützt auf ein stilisiertes theoretischen Model und einen umfassenden Datensatz zu Immobilienanzeigen untersucht dieser Artikel den kausalen Effekt der Veröffentlichung von Energieverbrauchsinformationen auf Angebotspreise. Ein besonderer Schwerpunkt liegt auf der Untersuchung, ob diejenigen Hausverkäufer, die Energieverbrauchsinformationen nicht freiwillig veröffentlichen, Ihre Angebotspreise senken, sobald die Veröffentlichung verpflichtend wird. Die Analyse nutzt Panel-Methoden und einen Instrumentvariablen-Ansatz um die potenzielle Endogenität der Veröffentlichungsentscheidung zu berücksichtigen. Unsere Ergebnisse unterstreichen die Effektivität von Veröffentlichungspflichten zur Erhöhung der Markttransparenz und zur Senkung von Preisen.
Keywords: D82; L15; Q58; 330; information asymmetry; mandatory disclosure; environmental certification